Challenges of Conflict of Laws in the Digital Environment: An Analytical Study of Online Contracts - Al-Mawla, Taha (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2025)
In recent years, the Internet has created not only a binding concept of time and place, but also a new significant social structure. Utilization of the Internet is not a privilege of certain countries; rather, it is a necessity for modern survival. Nowadays Internet influence is strongly growing in economic and political areas worldwide leading to the globalization of these fields. The influence of the Internet is viewed differently by countries, thereby creating various dangers. For instance, the constant worldwide communication could significantly deteriorate countries’ relationships and therefore, national security. The Internet is not as significant for the economy as states see it, which are unaware of its potential. Instead, major information systems, electronics companies and the main stock exchanges are controlled by a few countries, while other countries are only consumers, losing the greatest economic profit. The Internet creates both desired and undesirable objects for the countries; however, the latter are not successfully neutralized. Some valid and relatively modern conflicts of laws conventions are reviewed including certain conventions and directives on electronic commerce. Some provisions of these acts are seen as a possibility for further developing a more cognition-oriented disposition of the Internet global nature as opposed to its territorial understanding. The mentioned rules could be supplemented by creating interoperability, traceability, functionality and other technical characteristics on the web. The rapid development of information technology challenges judicial and legal systems around the globe. New opportunities and possibilities of high-tech electronic transfers of data, messages and documents lead to disputes in cyberspace that need to be settled in court. For example, a person subscribes to an online newspaper evening edition in a certain location and is charged through an unauthorized credit card instruction in another location. The contract was concluded in both states and in a third one, nowhere and everywhere. The question arises: can and where to sue the newspaper? Or through a scorched access to the e-mail address: legality of derogatory statements about a local mayor and arising attempts from another location, where no mail is deliverable? Or through an exceedingly unsafe chat room riddled with offensive gender comments of a security guard? In these four hypothetic cases, clearly a search engine is crucial; nevertheless, it is registered in a region where access is easy. States try now to regulate this and other acts or facts occurring outside their territory. Their attempts seem culminative, as, for example, the criminal exodus of certain individuals from one country stopped after a worker’s upset retire to another country. The state will probably expect that issuing of requests will end, without realizing that anomalous behavior is incidental from a new way of thinking that charters and titles are of little or no value in a number of occasions boundaries. Additionally, other states may wish to efflux sophisticated suspicions on their territory, since presumably certain entities are deep within their own country as well as in others; nevertheless, its painstaking behavior may cause amazement again